PHANGS: constraining star formation time-scales using the spatial correlations of star clusters and giant molecular clouds. Issue 3 (11th September 2022) - Turner, Jordan A; Dale, Daniel A; Lilly, James; Boquien, Mederic; Deger, Sinan; Lee, Janice C; Whitmore, Bradley C; Anand, Gagandeep S; Benincasa, Samantha M; Bigiel, Frank; Blanc, Guillermo A; Chevance, Mélanie; et al.
ABSTRACT: In the hierarchical view of star formation, giant molecular clouds (GMCs) undergo fragmentation to form small-scale structures made up of stars and star clusters. Here we study the connection between young star clusters and cold gas across a range of extragalactic environments by combining the high resolution (1″) PHANGS–ALMA catalogue of GMCs with the star cluster catalogues from PHANGS– HST . The star clusters are spatially matched with the GMCs across a sample of 11 nearby star-forming galaxies with a range of galactic environments (centres, bars, spiral arms, etc.). We find that after 4 − 6 Myr the star clusters are no longer associated with any gas clouds. Additionally, we measure the autocorrelation of the star clusters and GMCs as well as their cross-correlation to quantify the fractal nature of hierarchical star formation. Young (≤10 Myr) star clusters are more strongly autocorrelated on kpc and smaller spatial scales than the $\gt \, 10$  Myr stellar populations, indicating that the hierarchical structure dissolves over time.